Analisis Qaulan Sadida Terhadap Penanaman Kejujuran Siswa (Studi Kasus: Siswa Kelas VII MTs Al-Mubarok Cisalak) - Afif Nurseha; Rizki Rizaulhaq (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
word that is far from lies and does not make up words that are made up by someone. It is undeniable that honest words are something that the Prophet Muhammad SAW liked in this era of globalization as now honest words are very poorly understood by young people or millennials. The problems discussed in this study are about the influence of Qaulan sadida on the cultivation of honesty values and about communication ethics. In today's era there are lots of people who pay less attention to honesty and instill values from an early age, communicating does not precede ethics, more concerned with the will of their passions to speak so that communication between individuals does not have significant values in the communication. That communication is the main urgency to socialize and also to raise high ideals. The research method used is descriptive qualitative method of collecting data by means of observation, interviews and documentation. The conclusion in the thesis entitled Analysis of qaulan sadida on the inculcation of students' honesty values is that it can foster a sense of students' honesty values to become more serious learning motivations. Instilling honesty values in seventh grade students at MTs A-Mubarok Cisalak, namely teachers must be more active in assisting students in activities that form honesty in students. Students who have a high sense of honesty will have the initiative to learn.